2019
DOI: 10.1039/c9ta00741e
|View full text |Cite
|
Sign up to set email alerts
|

Necklace-like MoC sulfiphilic sites embedded in interconnected carbon networks for Li–S batteries with high sulfur loading

Abstract: The small MoC nanoparticles grown on the surface of interconnected carbon networks work as effective sulfiphilic sites, helping to achieve a high electrochemical performance for Li–S batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 52 publications
2
41
0
Order By: Relevance
“…Given that several researchers have investigated the usage of BC in the interlayer of LSBs, investigations have also consistently demonstrated that BC‐based composites serving as the sulfur hosts can effect high performance. Shi et al . prepared a necklace‐like N‐CBC/MoC film by the freeze‐drying and solid‐state thermal reaction.…”
Section: Application Of Flexible Bc‐based Materials In Energy Productsupporting
confidence: 87%
See 2 more Smart Citations
“…Given that several researchers have investigated the usage of BC in the interlayer of LSBs, investigations have also consistently demonstrated that BC‐based composites serving as the sulfur hosts can effect high performance. Shi et al . prepared a necklace‐like N‐CBC/MoC film by the freeze‐drying and solid‐state thermal reaction.…”
Section: Application Of Flexible Bc‐based Materials In Energy Productsupporting
confidence: 87%
“…f) Cycling stability (150 cycles) and coulombic efficiency of the N‐CBC/MoC/Li 2 S 6 electrode with a sulfur loading of 4 mg cm −2 at a current density of 1.0 C. Reproduced from ref. with permission; copyright 2019, Royal Society of Chemistry.…”
Section: Application Of Flexible Bc‐based Materials In Energy Productmentioning
confidence: 98%
See 1 more Smart Citation
“…Other carbides, such as B 4 C, [296,297] Mo 2 C, [298][299][300] MoC, [301,302] NbC, [84,303] and WC, [304] have also been investigated as sulfur host. For example, Luo et al designed a simple catalyst-assisted approach to grow B 4 C nanowires at CNFs.…”
Section: Other Carbidesmentioning
confidence: 99%
“…Similar with the plant based cellulose substances, the bacterial cellulose substance owns unique three‐dimensional network structures that composed of nanofibers within diameter below 100 nm, which ensures good electrochemical performances when it is employed as the carbon resource of the electrode materials for Li−S batteries [49] . For example, a necklace‐like molybdenum carbide/N‐doped carbon nanofiber (MoC@N‐CNF) composite was fabricated through the ion impregnation, freeze‐drying and solid‐state thermal reaction processes by employing the bacterial cellulose as both interconnected carbon networks and supporting framework for impregnated molybdate ions [50] . The ultrafine MoC nanoparticles with a size of ca .…”
Section: Natural Cellulose Substances Based Carbon Materials For Lithmentioning
confidence: 99%